STRATEGI PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BERBASIS EKONOMI KREATIF DI KELURAHAN BABAKAN KECAMATAN SANDUBAYA KOTA MATARAM - Ainun Nisa; Muhammad Sayuti; Mimi Cahayani; Istiharah; Ulum, Miftahul (Jurnal Kompetitif : Media Informasi Ekonomi Pembangunan, Manajemen dan Akuntansi, 2024)
The results of this research are that social capital, in this case the elements of social capital, consist of participation in a network, namely through family, friends, relatives, even neighbors and also through social media as a means for them to expand their business network. ; reciprocity, where they prioritize collaboration rather than competition; trust, they always maintain communication and provide good service to customers, by maintaining their attitude and words; social norms, the rules they use are the rules that have been taught by their parents and religion, such as rules for social relations. These social relations rules include rules for speaking, behaving (ethics and responsibility), and interacting with others; and value, namely in the form of product quality, innovation and creativity, regarding product quality, home industry players really prioritize product quality in terms of taste, cleanliness and tidiness of the product, regarding innovation and creativity are still minimal, especially in terms of product packaging which is still traditional. So, most of the elements of social capital have been implemented by home industry players in the Tembelok area in running their businesses, and this social capital has resulted in sustainable sustainability of their businesses.